2018
DOI: 10.1186/s12887-018-1188-6
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of preemptive fluid strategy as a bundle to prevent fluid overload in children with acute respiratory distress syndrome and sepsis

Abstract: BackgroundFluid overload (FO) is associated with unfavorable outcomes in critically ill children. Clinicians are encouraged to avoid FO; however, strategies to avoid FO are not well-described in pediatrics. Our aim was to implement a bundle strategy to prevent FO in children with sepsis and pARDS and to compare the outcomes with a historical cohort.MethodsA quality improvement initiative, known as preemptive fluid strategy (PFS) was implemented to prevent early FO, in a 12-bed general PICU. Infants on mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 55 publications
(54 reference statements)
1
29
0
5
Order By: Relevance
“…27 Fluid creep has previously been observed in critically ill infants and children 4 ; however, little emphasis has been placed on the significance of its contribution given the current research focus on restrictive resuscitation and maintenance fluid strategies. 28,29 The majority of patients in this study developed hyperchloremia within the first 72 hours of PICU admission. Hyperchloremia and HCMA have not been well studied in the general PICU population.…”
Section: Discussionmentioning
confidence: 91%
“…27 Fluid creep has previously been observed in critically ill infants and children 4 ; however, little emphasis has been placed on the significance of its contribution given the current research focus on restrictive resuscitation and maintenance fluid strategies. 28,29 The majority of patients in this study developed hyperchloremia within the first 72 hours of PICU admission. Hyperchloremia and HCMA have not been well studied in the general PICU population.…”
Section: Discussionmentioning
confidence: 91%
“…Although we cannot draw conclusions of the effect of these specific fluid strategies for other patient populations based on this study, it could be hypothesized that patients with sepsis or severe acute respiratory distress syndrome and therefore more risk of capillary leak and/or AKI, will show a different response in terms of fluid balance upon use of similar fluid strategies. A recent implementation study in children with acute respiratory distress syndrome or sepsis has shown that the combination of fluid restriction, drug volume reduction, dynamic monitoring of preload markers to determine the need for fluid bolus administration, early use of diuretics and early initiation of enteral feeds decreased fluid overload and mechanical ventilation duration (28). However, this study was a retrospective cohort and a future RCT in the future might provide more robust evidence.…”
Section: Figure 4 |mentioning
confidence: 82%
“…FO is an iatrogenic and modifiable risk factor, yet the construct of FO is not included in the NCI CTCAE versions 4.0 or 5.0. Furthermore, FO is not consistently described in the pediatric literature, with definitions typically relating to daily fluid balance, percent weight change from baseline, and physical exam findings. At initial presentation, pediatric acute leukemia patients have historically received hyperhydration in an effort to prevent hyperuricemia‐induced renal injury and leukostasis complications, a practice that may place patients at risk for iatrogenic FO, pulmonary edema, and preventable respiratory AEs.…”
Section: Discussionmentioning
confidence: 99%
“…Lung ultrasound is an inexpensive, low risk, highly accessible method shown to be effective in quantifying extravascular lung volume in patients at risk for pulmonary edema. 45,46 Conservative, net-neutral, fluid balance strategies have been successful in a number of pediatric patient populations, including stem cell transplant recipients, 35 ARDS patients, 34,43 and post-resuscitation sepsis patients. 34,43 In a meta-analysis of 11 randomized trials incorporating conservative versus standard/liberal fluid strategies in the post-resuscitative care of adults and children with ARDS, sepsis, or systemic inflammatory response syndrome, a conservative strategy was associated with increased ventilator-free days and decreased ICU stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation